Peroxiredoxin 6 maintains mitochondrial homeostasis and promotes tumor progression through ROS/JNK/p38 MAPK signaling pathway in multiple myeloma - Dandan Gao; Yang Lv; Fei Hong; Dong Wu; Ting Wang; Gongzhizi Gao; Zujie Lin; Ruoyu Yang; Jinsong Hu; Aili He; Pengyu Zhang (Scientific Reports)
Abstract Peroxiredoxin 6 (PRDX6) is one of the Peroxiredoxin family members with only 1-Cys, using glutathione as the electron donor to reduce peroxides in cells. PRDX6 has been frequently studied and its expression was associated with poor prognosis in many tumors. However, the expression of PRDX6 in multiple myeloma (MM) and its relevance with MM remain unclear. In our study, we found that PRDX6 was overexpressed in MM patients. Its high expression was inversely correlated with prognosis but positively correlated with the levels of β2-microglobulin (B2M), lactate dehydrogenase (LDH), and International Staging System (ISS) stage of MM patients. Further, the deficiency of PRDX6 promoted MM cell lines (RPMI 8226, MM.1S, and U266) apoptosis significantly. Mechanically, PRDX6 serves as an anti-oxidative enzyme, and its deficiency led to over-accumulation of reactive oxygen species (ROS), resulting in oxidative stress, following the activation of MAPK signaling pathway, which manifested as phosphorylation of JNK and p38. Then, the expression of BAX and Bcl2 was imbalance, and the cascade cleavage of PARP and caspase 3 was increased, ultimately triggering cell apoptosis. In addition, oxidative stress decreased mitochondrial membrane potential (MMP), reduced gene expression levels of oxidative phosphorylation (OXPHOS), and increased in the density of mitochondrial crumpling, leading to mitochondrial structural abnormalities and dysfunction. Furthermore, PRDX6 deficiency combined with bortezomib induced a robust anti-tumor effect in MM cell lines. Finally, in vivo experiments also showed that the deficiency of PRDX6 inhibited tumor growth of tumor-bearing mice. Collectively, PRDX6 protects MM cells from oxidative damage and maintains mitochondrial homeostasis. And targeting PRDX6 is an attractive strategy to enhance the anti-tumor effect of bortezomib in MM.